2009
DOI: 10.1017/s1481803500011787
|View full text |Cite
|
Sign up to set email alerts
|

“I never hear what happens, even if they die”: a survey of emergency physicians about outcome feedback

Abstract: Objective: Emergency physicians (EPs) rarely find out what happens to patients after the patients leave their care, a process we call “outcome feedback.” Some suggest this hinders the practice of emergency medicine (EM); however, evidence is lacking. We sought to evaluate EPs' perception of the current and potential role of outcome feedback in EM. Methods: We surveyed practising French- and English-speaking EPs from emergency departments wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 2 publications
2
28
0
Order By: Relevance
“…To the editor: I read with great interest Lavoie and colleagues' article regarding outcome feedback. 1 I agree with the findings that most emergency physicians would like more outcome feedback. More importantly, as Lavoie states in his editorial, 2 feedback on the outcomes of our decisions is vital to our becoming experts in our profession.…”
Section: Letters • Correspondance Outcome Feedback: An Opportunity Fosupporting
confidence: 86%
“…To the editor: I read with great interest Lavoie and colleagues' article regarding outcome feedback. 1 I agree with the findings that most emergency physicians would like more outcome feedback. More importantly, as Lavoie states in his editorial, 2 feedback on the outcomes of our decisions is vital to our becoming experts in our profession.…”
Section: Letters • Correspondance Outcome Feedback: An Opportunity Fosupporting
confidence: 86%
“…Lavoie et al suggested that greater feedback for staff emergency physicians could improve job satisfaction, clinical efficiency, diagnostic accuracy and treatment outcomes. 17 This belief was supported by the majority of residents and program directors in this study.…”
Section: Discussionsupporting
confidence: 55%
“…Additionally, very little has been published regarding the prevalence of passive outcome feedback within EM, but evidence suggests that it is low for both residents and staff physicians. 16,17 The study survey results reveal that there is currently no mandated follow-up of emergency department patients in residency programs; however, a majority of trainees voluntarily followed between 1-20% of patients that they had treated. Passive outcome feedback was rare, only being corroborated by residents in a single program.…”
Section: Discussionmentioning
confidence: 99%
“…an outpatient consultation reply, or a copy of the patient's discharge summary) occurred in a median of 10% of cases, whereas feedback was actively sought by the emergency doctor in a median of 5% of cases. 8 Although this might not be directly translatable to the Australian setting, we have little reason to believe that things are much different.…”
Section: Casementioning
confidence: 99%